An RxLR effector from Phytophthora infestans prevents re-localisation of two plant NAC transcription factors from the endoplasmic reticulum to the nucleus. - Hazel McLellan; Petra C Boevink; Miles R Armstrong; Leighton Pritchard; Sonia Gomez; Juan Morales; Stephen C Whisson; Jim L Beynon; Paul R J Birch (PLoS Pathogens)
The potato late blight pathogen Phytophthora infestans secretes an array of effector proteins thought to act in its hosts by disarming defences and promoting pathogen colonisation. However, little is known about the host targets of these effectors and how they are manipulated by the pathogen. This work describes the identification of two putative membrane-associated NAC transcription factors (TF) as the host targets of the RxLR effector PITG_03192 (Pi03192). The effector interacts with NAC Targeted by Phytophthora (NTP) 1 and NTP2 at the endoplasmic reticulum (ER) membrane, where these proteins are localised. Transcripts of NTP1 and NTP2 rapidly accumulate following treatment with culture filtrate (CF) from in vitro grown P. infestans, which acts as a mixture of Phytophthora PAMPs and elicitors, but significantly decrease during P. infestans infection, indicating that pathogen activity may prevent their up-regulation. Silencing of NTP1 or NTP2 in the model host plant Nicotiana benthamiana increases susceptibility to P. infestans, whereas silencing of Pi03192 in P. infestans reduces pathogenicity. Transient expression of Pi03192 in planta restores pathogenicity of the Pi03192-silenced line. Moreover, colonisation by the Pi03192-silenced line is significantly enhanced on N. benthamiana plants in which either NTP1 or NTP2 have been silenced. StNTP1 and StNTP2 proteins are released from the ER membrane following treatment with P. infestans CF and accumulate in the nucleus, after which they are rapidly turned over by the 26S proteasome. In contrast, treatment with the defined PAMP flg22 fails to up-regulate NTP1 and NTP2, or promote re-localisation of their protein products to the nucleus, indicating that these events follow perception of a component of CF that appears to be independent of the FLS2/flg22 pathway. Importantly, Pi03192 prevents CF-triggered re-localisation of StNTP1 and StNTP2 from the ER into the nucleus, revealing a novel effector mode-of-action to promote disease progression.